Privacy and Security Issues in Social Networking Sites (SNS) - Khatri, Naresh; Paudel, Sunil (Journal of Science and Engineering, 2021)
Social Networking Sites (SNS) have become very fashionable during the past decade, as they permit users to both express their personal feelings and meet friends, relatives, and people with similar interests. There are many potential threats to data privacy and security like fraud, identity theft, and disclosure of sensitive information. Many users are still not conscious of these threats. Moreover, the privacy settings provided by SNSs aren't flexible and reliable enough to protect user data. Users don't have any control over what others reveal about them. We conducted a preliminary study among internet users of Nepal which examines the privacy and security issues in SNSs because the users share their information and put varieties of data on SNSs. This study intends to protect the user information from any misuse, to make sure of data security, and to permit users to choose what information to share and with whom. Another objective of this study is to measure the level of steps taken by the SNS operators. We identified privacy and security issues in SNS and propose a Privacy and Security Framework as a foundation to deal with these problems.